(untitled) (Academia Journal of Medicine, 2020)
Background: Intensive care units (ICUs), despite advances in critical care nursing, have frequent issues with early diagnosis and adequate treatment. Recently discovered world-class procalcitonin (PCT), a revolutionary laboratory marker, has been shown to be useful in this regard. The objective is to Comparison of concentrations of serum procalcitonin (PCT) and c-reactive protein (CRP) with a comparable level of organ malfunction during sepsis and evaluation of the interaction between serum PCT and CRP concentrations with different organ malfunction occurrence in sepsis. Design: It is a Hospital-Based Prospective study. Participants and Setting: Fifty people were admitted to the intensive care unit of Gandhi Medical College. Subjects and Methods: The extent of sepsis-related organ impairment was evaluated with the sequential organ failure assessment (SOFA) on day 1. Patients were identified by category 1(0-6), category 2(7-12), group 3(13-18), and group 4(19-24) in 4 separate classes with varying organ impairment seriousness of sepsis. Serum PCT and CRP concentrations have been measured. Results: The majority of the patients belonged to the age groups of 60-69 years (30%) and 50-59 years (22%) Majority of the patients belonged to the Sofa group 1 around 42% followed by sofa group 2 with 38%, sofa group 3 with 16% and the least belonged to the sofa group 4 with 4%. The mean PCT and CRP concentration in those who survived was 14.73 ng/ml and 149.916mg/L respectively and in those who died were 45.76 ng/ml (p-value <0.001) and 183.584 mg/L (p-value 0.172) respectively. The linear correlation between PCT plasma concentrations and the four groups was significantly stronger than with CRP. Conclusion: In SOFA and serum PCT, The level of organ dysfunction and complications in sepsis patients is closely related to serum CRP levels.